広範な変性壊死を伴った顎下腺多形腺腫の1例 - 足立, 雅利; 白川, 正順; 柳下, 秀郎; 荘司, 洋文; 藤野, 能成; 柳下, 寿郎 (日本口腔外科学会雑誌, 2010)
Pleomorphic adenoma is the most frequent benign tumor arising in the major salivary glands.Histopathological findings of this tumor vary; however, extensive necrosis does not generally occur. We describe a 74-year-old woman with pleomorphic adenoma of the submandibular gland associated with extensive degenerative necrosis. She consulted our hospital because of a painless swelling that had persisted for 20 years in the right submandibular region. MRI revealed a mass with a distinct border in the right submandibular gland, associated with a low-signal-intensity area. The patient was given a diagnosis of pleomorphic adenoma of the right submandibular gland, and tumorectomy was performed under general anesthesia. Histopathological examination of the resected specimen showed a pleomorphic adenoma with extensive necrosis. During the 5-year postoperative follow-up, there has been no recurrence. Pleomorphic adenoma of the major salivary glands with extensive degenerative necrosis is very rare. Only 9 cases of this type of adenoma in the parotid gland have been reported. To our knowledge, this is the first such tumor arising in the submandibular gland to be reported.